2021
DOI: 10.7717/peerj.10581
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping tools and resources to assess peanut germplasm: smut-resistant landraces as a case study

Abstract: Peanut smut caused by Thecaphora frezii is a severe fungal disease currently endemic to Argentina and Brazil. The identification of smut resistant germplasm is crucial in view of the potential risk of a global spread. In a recent study, we reported new sources of smut resistance and demonstrated its introgression into elite peanut cultivars. Here, we revisited one of these sources (line I0322) to verify its presence in the U.S. peanut germplasm collection and to identify single nucleotide polymorphisms (SNPs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Although only stable QTLs across the 3 years of evaluation were considered in this study, the region with significant association found on LG B09 (9.35 Mbp - 10.97 Mbp) merits further attention as a block of 457 kb on chromosome Arahy.19 has been reported as a potential region associated with resistance to peanut smut [ 20 ]. The existence of diverse sources of genetic resistance is relevant for the development of varieties with more durable resistance to smut.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although only stable QTLs across the 3 years of evaluation were considered in this study, the region with significant association found on LG B09 (9.35 Mbp - 10.97 Mbp) merits further attention as a block of 457 kb on chromosome Arahy.19 has been reported as a potential region associated with resistance to peanut smut [ 20 ]. The existence of diverse sources of genetic resistance is relevant for the development of varieties with more durable resistance to smut.…”
Section: Discussionmentioning
confidence: 99%
“…Natural sources of resistance to smut found in some old peanut landraces and in wild relatives can be utilized to enhance peanut performance under high disease pressure [ 18 ]. The introgression of smut resistance into elite peanut lines and pre-breeding materials from landraces [ 19 , 20 ] and wild Arachis species [ 21 ] were recently reported by our research group. In Bressano et al [ 19 ], the recombinant inbred lines (RILs) involved crosses between three susceptible peanut elite cultivars ( Arachis hypogaea L. subsp .…”
Section: Introductionmentioning
confidence: 99%
“…For example, United States is a major exporter of peanuts [5], but it also imports peanuts from other countries [6] including Argentina [7]. Scientists from the U.S. and Argentina are working in collaboration to better understand the disease and to identify resistant peanut germplasm [8][9][10][11]. Part of that effort is to know the genetics of the pathogen.…”
Section: Objectivementioning
confidence: 99%
“…Single nucleotide polymorphisms (SNPs) are the most abundant DNA sequence variation in genomes and can be used as molecular markers to associate loci in the genome with phenotypic traits. Using these markers, Liang et al (2020) reported quantitative trait loci (QTLs) associated with Sclerotinia blight resistance; Pandey et al (2017) and Chu et al (2019) for early, late leaf spot and tomato spotted wilt virus resistance; Varshney et al (2014) for rust resistance, and de and Massa et al (2021) for peanut smut.…”
Section: Core Ideasmentioning
confidence: 99%